Complete chloroplast genome of Lamium takesimese Nakai (Lamiaceae): an endemic species in South Korea. Issue 2 (3rd July 2019) - Park, Kyu Tae; Shin, Jaehang; Park, Seonjoo
Abstract: The complete chloroplast genome of Lamium takesimense (Lamiaceae), an endemic species in South Korea, are presented in this article. The genome size is 150, 626 bp in length, with 38.6% of GC content. It consists a large single-copy (LSC) region (82, 527bp) and a small single-copy region (SSC) (17, 185bp) which were separated by two inverted repeat (IRs) regions (25, 457bp). The complete chloroplast genome contains 111 unique genes, including 77 protein-coding genes, 4 rRNA genes, and 30 tRNA genes.